(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
One of the most important tasks of contemporary democratic states, being simultaneously a real challenge for them, is guaranteeing a stable process of their dynamic and effective development, based on the democratic principles expressed in their constitutions jointly with their practical and effective implementation. Among others, one of the main states’ tasks is also guaranteeing fundamental rights and freedoms to its citizens and people, as well as enabling them their proper exercising and strict observance. The hereby paper aims at conducting a detailed legal analysis of the catalogue of fundamental principles contained in the Constitution of the Republic of Poland of 1997, being presently in force, along with reflecting over their content and scope, as well as discussing their sources and axiological basis deriving from the output of Polish constitutional law doctrine, the doctrine of other developed democratic states and international standards.